Pain evaluation and mitigation in the bovine - Yager, Alexandra Lee, author; Ahola, Jason, advisor; Peel, Richard, committee member; Whittier, Jack, committee member; Callan, Robert, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: mechanical nociceptive threshold; dairy cattle; pain mitigation; beef bulls; castration